MOTIVASI BELAJAR SISWA YANG GEMAR BERMAIN SEPEDA DI SD NEGERI 016 TANJUNG MEDAN TAHUN PELAJARAN 2013/2014 - Natariya MS, Deasy Natariya MS Deasy; Asyari, Abu Assyari Abu; Arlizon, Raja Arlizon Raja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstack Top of FormThis study titled "Joy of Learning Motivation Students in Elementary School Bicycle Playing Tanjung Medan 016 Academic Year 2013/2014". Of symptoms seen in 016 primary school students Tanjung Medan problems identified in this study is the students' motivation is disrupted by love to play bike. The purpose of this research are: 1) Knowing picture intrinsic motivation of students who love to play bike. 2) Knowing picture extrinsic motivation of students who love to play bike. 3) Knowing students' motivation level overview that likes to play bike. In this study, the authors used quantitative research methods with descriptive format. The population in this study is the overall student who likes to play in Class III bike 016 Tanjung Medan SDN Academic Year 2013/2014 by using random sampling techniques saturated / total. Based on the results of research and data processing which has been conducted by researchers, it can be concluded as follows: 1) The level of intrinsic motivation of students of SDN 016 Tanjung Medan who likes to play in the school year 2013/2014 bikes are mostly located in the middle category. 2) The level of extrinsic motivation of students of SDN 016 Tanjung Medan who likes to play bike 2013/2014 school year mostly likes to be in the medium category. 3) The activities of students who are affected because the bike likes to play most of the high category, activity less attention to the teacher's explanation and activity exhaustion / fatigue. 4) Thus the intrinsic and extrinsic motivation level student learning SDN 016 Tanjung Medan who likes to play in the school year 2013/2014 bike in middle category.Keywords: Motivation to learn, likes to play bike